Association between Hospital Birth Volume and Maternal Morbidity among Low-Risk Pregnancies in Rural, Urban, and Teaching Hospitals in the United States - Kozhimannil, Katy B.; Thao, Viengneesee; Hung, Peiyin; Tilden, Ellen; Caughey, Aaron B.; Snowden, Jonathan M. (American Journal of Perinatology, 2016)
Objectives This study aims to examine the relationship between hospital birth volume and multiple maternal morbidities among low-risk pregnancies in rural hospitals, urban non-teaching hospitals, and urban teaching hospitals, using a representative sample of U.S. hospitals.Study Design Using the 2011 Nationwide Inpatient Sample from 607 hospitals, we identified 508,146 obstetric deliveries meeting low-risk criteria and compared outcomes across hospital volume categories. Outcomes include postpartum hemorrhage (PPH), chorioamnionitis, endometritis, blood transfusion, severe perineal laceration, and wound infection.Results Hospital birth volume was more consistently related to PPH than to other maternal outcomes. Lowest-volume rural (< 200 births) and non-teaching (< 650 births) hospitals had 80% higher odds (adjusted odds ratio [AOR] = 1.80; 95% CI = 1.56–2.08) and 39% higher odds (AOR = 1.39; 95% CI = 1.26–1.53) of PPH respectively, than those in corresponding high-volume hospitals. However, in urban teaching hospitals, delivering in a lower-volume hospital was associated with 14% lower odds of PPH (AOR = 0.86; 95% CI = 0.80–0.93). Deliveries in rural hospitals had 31% higher odds of PPH than urban teaching hospitals (AOR = 1.31; 95% CI = 1.13–1.53).Conclusions Low birth volume was a risk factor for PPH in both rural and urban non-teaching hospitals, but not in urban teaching hospitals, where higher volume was associated with greater odds of PPH.
Keywords: maternal morbidity; birth volume; teaching hospitals; rural hospitals; postpartum hemorrhage